Management planting densities and application of efficient microorganisms that increase rice productivity - Hurtado, Alexander Calero [UNESP]; Viciedo, Dilier Olivera [UNESP]; Díaz, Yanery Pérez; Hurtado, Yainier González-Pardo; Simón, Lesly Analay Yánez; Calzada, Kolima Peña [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2020)
The use of adequate planting densities (D) it is an important parameter to increase rice grain productivity, on the other hand, the use of efficient microorganisms (EM) bio-prepared, can be an efficient alternative, for rice production in early planting season. Therefore, the objective of the present research was to compare different planting densities and to investigate the effect of the addition of efficient microorganisms in increasing rice yield. The experimental model corresponded to a randomized block design, in a factorial scheme (4 × 2), which consisted of four planting densities (25000, 35000, 45000, and 55000 plant ha–1) combined with the absence (0 mL L–1) and presence (100 mL L–1) of the bio-prepared of efficient microorganisms. The parameters evaluated were plant height (cm), tillers number, percentage of fertile tillers and full grains per panicle, number of panicles per m2, number of grains per panicle, length of panicle (cm), 1000-grains mass (g) and yield (t ha–1). The results showed significant effects of the interaction density × efficient microorganisms. Our findings indicated that the density of 45,000 plants ha–1 was more effective because increased grain yield by 84% the absence of ME and by 58% in the presence of ME relative to the lower density and was significantly higher than the others two densities. Our results indicate that the application of ME via soil enhances rice crop productivity. This was possible because the growth and development parameters evaluated were modified and, therefore, could lead to a sustainable increase in crop yield.
Manejo de diferentes densidades de plantación y aplicación de microorganismos eficientes que incrementan la productividad del arroz
Keywords: beneficial microorganism; Oryza sativa; Soil inoculation; Sowing distance; Yield